The Financial Implications of the Integration of two financing operations in a market place, Case Ford Financial Finland - Tolvanen, Jussi (My University, 2008)
The research problem in the study is to study the problematic behind a merger / integration of two companies and in the case study to concentrate on how to integrate a local finance company into an international finance company. In a merger two separate legal entities become one and both operations and accounting will be merged. This kind of restructuring has always very remarkable change effects for both companies so the management of both companies needs to evaluate all merger effects before the actual merger decision is made. In general it seems like mergers in Banking Sector very often generates net benefits. In this study I have evaluated real life case based on the existing Banking, M&A and Corporate Restructuring theories. On top of those I have used legal regulations and taxation & accounting frameworks. The basis for the case study was to see how the merger decision model proposed by Koskela (1993) is working in real case and also to see what are the differences between theoretically correct decisions and the real life decisions. First of all, the case study clearly showed the importance of careful evaluation of IT and tax costs before any merger decisions are made. It also showed that there are differences between theoretically correct decisions and real-life decisions. In this case study the major deviations from the theoretically correct decision came from the need to simplify the legal structure and administration. Also the will to utilize strategic platforms and at the same time ensure corporate governance aspects created certain deviations. It seems like in reality merger decisions are impacted by corporate strategies and policies. Also management perception of the merger situation is extremely important factor. These factors cannot be measured by using general merger decision model.
Keywords: Mergers; Acquisitions; M&A; Banking; Integration; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|